2018
DOI: 10.5530/pj.2018.2.37
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Chemoprotective Effect of Quercetin from Argyreia speciosa against N-methyl-N-Nitro-N-Nitrosoguanidine and NaCl-Induced Gastric Carcinomas in Wistar Rats

Abstract: Objectives: This study was carried out to investigate the chemo protective potential of Quercetin, an isolated compound from Argyreia speciosa, on N-methyl-N-nitro-N-nitrosoguanidine and NaCl-induced gastric carcinomas in Wistar rats. Methods: The rats were fed with a diet supplemented with 8% NaCl and simultaneously given N-methyl-N-nitro-N-nitrosoguanidine. After administration of the carcinogen, quercetin was administered. The whole stomach and a part of duodenum were sampled, cut open and tumors were recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Quercetin isolated from ethanolic leaf extract and administered at dose of 100, 200 and 400 mg/kg. The results indicated that the quercetin therapy dosedependently stimulates immunity activity in rats and have declared influence on survivin which is an attractive target for the therapy of gastric cancer 50 . Kaur and colleagues find that hydroalcoholic root extract showed decreased HCl-induced lung inflammation in a dose-dependent fashion.…”
Section: Anticancer Activitymentioning
confidence: 97%
“…Quercetin isolated from ethanolic leaf extract and administered at dose of 100, 200 and 400 mg/kg. The results indicated that the quercetin therapy dosedependently stimulates immunity activity in rats and have declared influence on survivin which is an attractive target for the therapy of gastric cancer 50 . Kaur and colleagues find that hydroalcoholic root extract showed decreased HCl-induced lung inflammation in a dose-dependent fashion.…”
Section: Anticancer Activitymentioning
confidence: 97%